International trade law e-casebook - GAO, Henry S. (Institutional Knowledge at Singapore Management University, 2023)
The casebook on international trade law is currently in its open beta version, with 17 core chapters ready and the final four chapters to be added soon. However, we believe the book is now sufficiently advanced to prove potentially useful to students and teachers alike.